Sulfonated Graphene‐Oxide as Metal‐Free Efficient Carbocatalyst for the Synthesis of 3‐Methyl‐4‐(hetero)arylmethylene isoxazole‐5(4H)‐ones and Substituted Pyrazole. Issue 2 (17th January 2020) - Basak, Puja; Dey, Sourav; Ghosh, Pranab
Abstract: A straightforward, simple and unprecedented transformative protocol has been accomplished towards furnishing a wide variety of pharmaceutically promising functionalised 3‐methyl‐4‐(hetero)arylmethylene isoxazole‐5(4 H )‐ones and 6‐Amino‐3‐methyl‐4‐phenyl‐1, 4‐[2, 3‐c]pyrazole‐5‐carbonitriles. Sulfonated graphene oxide (SGO), a new class of heterogeneous carbocatalyst, was found to be efficient for thisone pot rapid conversion of isoxazoles and pyranopyrazoles from aldehyde. The prepared SGO was characterised by FEG‐SEM, HR‐TEM, FTIR and was recyclable up to 5 th run without a significant drop in its catalytic activity. Metal free synthesis, good to excellent yield, high atom economy, usage of readily available starting material, operational simplicity, easy workup, and recyclable catalyst are the fundamental features of this protocol. Abstract : Sulfonated graphene oxide, a promising solid acid catalyst was proved to be efficient for the one pot synthesis of substituted isoxazolones and pyranopyrazoles. Considering the novelty of our protocol, water a green solvent and SGO, a green carbocatalyst was used, thereby eliminating the hazourdous of toxic metals. A one‐pot easy synthesis of SGO was also established and the prepared catalyst was recycled upto several runs without decrease in its activity.